‘HOTS’ in Reading Comprehension Questions of English Textbook for Secondary School (Revised Bloom’s Taxonomy study) - Sri Mujayanah; Dewi Rosaria Indah; Apsari Fajar Prihantini; Yulis Setyowati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The objective of this research was to picture out the implementation of the three up levels of the cognitive domain of revised Bloom’s Taxonomy used in the reading comprehension questions of Complete English for Cambridge Secondary 1, namely analyzing level, evaluating level, and creating level. Using the descriptive qualitative method, this study examined the questions in the reading comprehension questions of the Complete English for Cambridge Secondary 1 published by Oxford University Press – Oxford, United Kingdom, in 2016, arranged by Dean Roberts, Jane Arredondo, Annabel Charles, Alan Jenkins, & Tony Parkinson to categorize the reading comprehension questions into HOTs levels.   A Revised Bloom's taxonomy-based checklist was utilized to gather, list, and classify these questions according to their cognitive levels. Then, for each level, the percentages were computed and finally described in account paragraphs. The findings of this study confirmed that Oxford University Press is a creditable publisher which accommodates HOTS in reading comprehension exercises based on the revised Bloom Taxonomy. The result showed that the most dominant level in the textbook was higher-order thinking skills (HOTS) was analyzing level in 50%. Then the evaluation reached 30% and creating reached got 20%. Additionally, this research has consolidated the confirmation base for using the Revised Bloom’s Taxonomy as a framework for revealing cognitive processes included in the high-order thinking skills.